Tradisi Pembacaan Surah Al-Insyirah Sebagai Wirid Dalam Shalat (Kajian Living Qur’an di Pondok Pesantren Tahfidzul Qur’an Putri Al-Lathifiyyah Palembang) - syarifatun nikmah; Uswatun Hasanah; Rahmat Hidayat (Al-Misykah: Jurnal Studi Al-qur'an dan Tafsir, 2021)
This study aims to determine the basis of the practice of reading pray Al-Insyirah at PPTQ Putri Al-Lathifiyyah Palembang, in order to explain how the procession of implementation, understanding, and meaning is felt by pray practitioners as well as how the reception of female students towards the tradition of reading pray Al-Insyirah. This type of research is field research using the living Qur'an method. As for the data analysis technique in this study using phenomenological description analysis. After conducting a study in this study, it was found that the asbab an-nuzul from the surah Al-Insyirah and the diploma from the cleric Adlan Ali to Ustadzah Lailatul Mu'jizat. M.Ag and then certificated to all female students which is the reason for making the pray reading routines for the female students. Technically, the procession of carrying out the tradition of reading pray Al-Insyirah begins with fardhu prayers in congregation and continues with reading istighfar, tahlil, allahumma anta salam, Al-Fatihah, Al-Insyirah, verse chairs, prayers, and ends with reading Asmaul Husna. As for the meaning that has been felt by wirid practitioners, especially the caretakers of cottage and Student, when they routinely recite the pray surah Al-Insyirah from the results of previous interviews with him, namely, as a form of inner intermediary so that all their affairs are facilitated, the process of memorizing and learning is facilitated, forming an optimistic and patient person, and namely as a medicine for a narrow heart because of many problems and not knowing the way out.